Relapse of Neonatal Escherichia coli Meningitis: Did We Miss Something at First? - Nadja H. Vissing; Mette B. Mønster; Sannie Nordly; Gholamreza K. Dayani; Sofie S. Heedegaard; Jenny D. Knudsen; Ulrikka Nygaard (MDPI AG, 2021)
Relapse of neonatal meningitis is most commonly caused by Escherichia coli. Management to prevent relapse varies and evidence is limited. We present four cases of relapsing neonatal E. coli meningitis in Denmark in 2016-2017 and review the current literature on this subject. During the primary episodes, our patients received cephalosporin for 3 weeks and gentamicin for the first 3 days. The only identified risk factor was delayed CSF sterilization in three of four cases and no repeated lumbar puncture. Relapse occurred after 2-28 days; one case with ventriculitis and one with empyema. Relapses were treated for 6-14 weeks with monotherapy. No children had an underlying disease predisposing to E. coli meningitis. There is generally a trend towards reducing invasive procedures, e.g., lumbar puncture and the length of intravenous antibiotics in pediatric infectious diseases, but our cases highlight a condition where the opposite might be needed.